Increasing the Number of Medical Emergency Calls Does Not Improve Hospital Mortality. Issue 7 (July 2018) - Santamaria, John; Moran, John; Reid, David
Abstract : Objectives: Medical emergency teams were established to rescue patients experiencing clinical deterioration thus preventing cardiac arrest and unexpected hospital mortality. Although hospitals are encouraged to increase emergency calling rates to improve in-hospital mortality, there are increasing concerns about the impact these calls have on the workload of the teams and the skill levels on the general wards. We set out to examine the relationship between emergency calling rates and adjusted in-hospital mortality. Design: Retrospective analysis of prospectively collected patient and emergency call data. Setting: Tertiary, metropolitan, and regional hospitals in the State of Victoria, Australia. Patients: Consecutive patients discharged from 1) St Vincent's Hospital Melbourne from January 2008 to June 2016 and 2) 15 Victorian hospitals from July 2010 to June 2015. Measurements and Main Results: We studied 441, 029 patients from St Vincent's Hospital Melbourne. Median age was 61.0 years (interquartile range, 45–74 yr), 57.2% were men, and 0.70% died; monthly emergency calling rates varied between 9.21 and 30.69 (median 18.4) per 1, 000 discharges. In-hospital mortality adjusted for age, gender, emergency status, same day admission, year of discharge, and Charlson Comorbidity Index was not reduced by higher calling rates in the month of discharge (odds ratio, 1.019; 95% CI, 1.008–1.031). We then examined 3, 339, 789 discharges from 15 Victorian hospitals with median age 61 years (interquartile range, 43–74 yr), 51.4% men, and hospital mortality 0.83% where yearly emergency calling rates varied from 18.46 to 33.40 (median, 25.75) per 1, 000 discharges. Again, adjusted mortality was not reduced by higher calling rates in the year of discharge (odds ratio, 1.003; 95% CI, 1.001–1.006). Conclusions: With adjustment for patient factors, illness, and comorbidities, increased emergency calling rates were not associated with reduced in-hospital mortality. Efforts to increase calling rates do not seem warranted. Abstract : Supplemental Digital Content is available in the text.